Guest Editors' Introduction - Daniel Shrubsole; Laura Murphy (International Indigenous Policy Journal, 2012)
We are very pleased to present the International Indigenous Policy Journal’s special edition on Water and Indigenous Peoples. The idea behind the special edition was to address the complications and nuances of the relationship between Indigenous peoples and water. While not exhaustive of all the issues regarding Indigenous peoples and water, we have been mindful to include in this edition papers that address many of the key indicators of unsafe drinking water on Indigenous reserve communities.We feel that this edition successfully interrogates why many reserves are still out of reach of safe drinking water, and we hope that the insights offered open up further dialogue and possibilities for meaningful and useful policy in the future.